Gross violations of human rights by the Apartheid regime under international law - Hinds, Lennox S.. (International Association of Democratic Lawyers New DelhiUS, 1998)
Reviews the apartheid legal system during those years in which as a matter of law all economic, political and social rights were reserved for the 17% of the European population who were legally classified as whites. Analyzes the crimes of apartheid against international norms of human rights law and characterizes them as the planned and premediated criminal practices of the apartheid government to maintain control and not merely the individual wrong doing of a few renegade security. Considers the culpability of lawyers and judges who condoned theis system.